Factors Affecting Inclusive Development in Nepal (Nepalese Journal of Development and Rural Studies, 2019)
The pathways of Nepal's inclusive development date long back. Since the inception of periodic economic development plan in the middle of the fifties, the country has been enduring goals for reforming just and equitable society. In the successive periodic plans, the objectives sharpened further. Yet, the country endorsed inclusive strategies and policies in par with global trends since the tenth plan (2002-2007). In this respect, this paper shortly reviews the concept of inclusive growth and inclusive development and juxtaposes these to elucidate factors causing Nepal's inclusive development. It analyses the country's macro-economic indicators to scrutinize them for their role in ensuring inclusive growth and development. The paper concludes that the country's fluctuating, polarized growth and weakening macro-economic indicators have been posing challenges to the inclusive development.